WHO Expert Committee on Drug Dependence : twenty-third report, meeting held in Geneva from 22 to 28 April 1986 - WHO Expert Committee on Drug Dependence; World Health Organization (Geneva : World Health Organization, 1987)
Assesses data on 31 barbiturates in order to determine which of these substances should be recommended for international control. Barbiturates are classified in three main groups: ultra-short-acting barbiturates used as intravenous anaesthetics or for the induction of anaesthesia, the intermediate-acting barbiturates used mainly as hypnotics and daytime sedatives, and other longer-acting substances used in the management of epilepsy. Five of the 31 substances are recommended for placement in Schedule III or IV. A concluding section, devoted to recommendations for improving review procedures, discusses the problems caused by the difficulty of obtaining phenobarbital in many developing countries, especially in view of the effectiveness of this Schedule IV substance in the treatment of epilepsy.
Introduction -- 1. General Considerations -- 2. Methods used in assessing the thirty-one barbiturates -- 3. assessment of individual substances -- 4. Recommendations
Keywords: Substance-Related Disorders; Barbiturates; Community Health and Primary Health Care